Mother-infant interaction patterns within the course of an early parenting training - Maike Heiser (2022)
Background: The transition to parenthood is an existential change and can lead to positive as well as negative long-term consequences. Early attachment between parent and child is one of the most important conditions for the entire later life. Numerous factors can influence early parent-child attachment. Parent education programs can support and empower parents to respond sensitively and individually to their child in order to promote the development of a secure attachment. Monitoring the effectiveness of these programs is of high importance in order to make interventions as targeted and sustainable as possible. Objectives: This study aims to examine the mother-child interaction changes throughout the parent education program "Sicherer Hafen". Methods: This Panel study with repeated measurement analysed 51 videos of mothers aged 21 to 40 years and their children aged 2 to 16 months (N=17). Using the method Coding Interactive Behaviour, mother-infant interaction was evaluated at three time points by three independent coders. An interrater- reliability assessment and repeated measurement ANOVA with post-hoc test was performed. Results: The assessment shows a significant positive improvement of the mother-child interaction patters in the categories Parent intrusiveness, Child social involvement and Dyadic reciprocity. For the categories Parental sensitivity and Child withdrawal did no significant results were found, but a positive trend based on the mean scores can be observed. Conclusion: This study shows the positive course of the mother- child interaction patterns within the parenting training "Sicherer Hafen". Nevertheless, no causal associations to the parenting training, or other influencing factors can be drawn. Further studies, including the mother's attachment experiences, the child's temperament, the relationship to the partner, and the contents of the counselling, are recommended. Further establishment of such prevention courses is essential to protect children, to support their right to health and to prevent maltreatment and violence.